Polychlorinated dibenzodioxins, dibenzofurans and non-ortho substituted polychlorinated biphenyls in caribou (Rangifer tarandus) from the Canadian Arctic - Hebert, C.E. (Craig); Gamberg, M. (M.); Elkin, B.T. (B. T.); Simon, M. (M.); Norstrom, R.J. (R. J.) (Science of The Total Environment, 1996)
The presence of contaminants in the Arctic environment has raised concerns regarding levels in wildlife and possible effects on the health of wildlife populations. In addition, contaminants in wild foods are of particular concern to those people who rely on these foodstuffs for a significant portion of their diet. Among the most toxic contaminants found in the environment are the polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs) and non-ortho substituted polychlorinated biphenyls (NOPCBs). Few data exist documenting the levels of these compounds in Arctic terrestrial wildlife. In 1993, caribou samples were obtained from three herds in the Yukon Territory (Finlayson, Tay and Bonnet Plume) and from four herds in the Northwest Territories (Bathurst, Southampton Island, Cape Dorset and Lake Harbour). High resolution gas-chromatography/mass spectrometry was used to measure contaminant concentrations. Wet weight concentrations of PCDDs, PCDFs and NOPCBs were greater in fat tissue than in muscle and liver, however, concentrations in all tissues were extremely low. Lipid normalized concentrations were greater in muscle and liver than in fat, indicating that equilibrium partitioning is not the only process regulating tissue concentrations of these contaminants. There were no significant relationships between concentrations of individual congeners and caribou age. Concentrations of the non-ortho substituted PCBs #126 and #169 were greater in caribou from the eastern Arctic, although levels in all herds were low. 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) toxic equivalents were also